Improving IPS Learning Outcomes by Using the Demontrative Method in Class V Students of SDN 08 Singaparna Rmbah for the 2017-2018 Academic Year - Ai Komariah (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the social studies learning process in class V SDN 08 Singaparna , the students were less active in learning and there were some students who did not pay attention to the teacher who was explaining and the grades of the students in the class were still not sufficient for the KKM. For this reason, it is necessary to improve learning in accordance with the circumstances of students and the material being taught from the lecture method to the demonstration method. The subjects of this study were students of class V SDN 08 Singaparna Tasikmalaya , totaling 30 people. The type of research that will be conducted is classroom action research. The implementation procedure consists of planning, implementing, observing and reflecting. Meanwhile, as an assessment tool in this study, it is in the form of student assignments and Teacher Ability Assessment Tools (APKG). The results of the study showed that students' abilities increased as evidenced by the increase in student scores from cycle to cycle. In cycle 1 the average value of children (68.33) while in cycle 2 the average increased to (81.33) and reached 100% completeness. With these results, it can be concluded that the demonstration method can improve student learning outcomes in science subjects.